Peripheral plaque burden in the diagnosis of coronary atherosclerosis in rheumatoid arthritis - O. A. Fomicheva; T. V. Balakhonova; O. A. Pogorelova; M. I. Tripoten; F. F. Shingareeva; S. O. Kuzyakina; E. B. Yarovaya; E. V. Gerasimova; T. V. Popkova; Yu. A. Karpov; E. L. Nassonov (Российский кардиологический журнал)
Aim. To assess plaque burden according to peripheral artery ultrasound examination in patients with rheumatoid arthritis (RA) with low and moderate disease activity in comparison with the coronary artery condition.Material and methods. The study included 64 patients, of which 43 patients with an established diagnosis of RA and 21 patients with coronary artery disease (CAD) without RA (comparison group). All patients underwent a clinical and paraclinical examination to verify myocardial ischemia and/or CAD according to the 2020 national guidelines, as well as a carotid and femoral artery ultrasound (the latter, only for patients with RA) with determination of plaque burden.Results. In patients with RA in combination with CAD, plaque burden is higher than in patients with RA without coronary artery disease regarding the carotid plaque number 4,0 [4,0; 5,0]/2,0 [1,0; 3,5], proportion of maximum stenosis 35,0 [35,0; 45,0]/30,0 [25,0; 35,0] and the proportion of total stenosis 120,0 [110,0; 152,5]/85,0 [40,0; 110,0]. Three or more carotid plaques determine significant coronary atherosclerosis in RA. In RA patients with CAD, the combination of carotid and femoral plaques is associated with significant coronary atherosclerosis in 75% of cases. In a comparative analysis of patients with RA CAD+/RA CAD-, no significant differences were found in the main cardiovascular risk factors, lipid, and inflammatory parameters. When comparing the plaque burden indicators, the severity of coronary atherosclerosis was not revealed between RA patients with CAD+ and the comparison group.Conclusion. Determining the peripheral plaque burden parameters increases the clinical significance of ultrasound as a stage of non-invasive CAD diagnosis in RA.